The Scientific- Spiritual Heritage of Aziziddin Nasafiyy and Its Study - Ibodilloyevich, Narziyev Zubaydillo (International Journal on Integrated Education, 2026)
This article explores the rich spiritual heritage of the great poet, physician, and philosopher Aziziddin Nasafiy, a distinguished figure who lived and worked in the 12th century. It examines his profound contributions to Sufi thought and highlights the enduring significance of his works. The study also notes that numerous Eastern and Western scholars have analyzed Nasafiy’s spiritual legacy, reflecting its wide-ranging influence across cultures and academic traditions. The article also traces the influence of Nasafiy’s ideas on later generations of scholars and mystics, both in the East and the West, demonstrating the universal relevance of his teachings. Furthermore, it highlights how his writings continue to inspire modern researchers interested in spiritual anthropology, metaphysics, and moral development.